The Analysis Study of Prevalence of Ruptur Uteri in Vaginal Birth After A Cesarean (VBAC): A Comprehensive Systematic Review - Hansen; Rafennia N.M Kakalang; Andrianto H.V Wongkar (The International Journal of Medical Science and Health Research, 2025)
Background: Uterine rupture (UR) is a significant concern in obstetrics, particularly for women attempting a vaginal birth after cesarean section (VBAC). This systematic review focused to analyze the prevalence of uterine rupture in women who undergo VBAC based on literature from the past decade. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2014 to 2024. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 630 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: Uterine rupture in VBAC is rare but linked to risks like labor induction, short interdelivery intervals, and maternal health. Enhanced patient selection, monitoring, and access to antenatal care can improve safety and outcomes, especially in resource-limited settings.